2015
DOI: 10.2135/cropsci2015.01.0020
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological Responses of Tall Fescue Genotypes to Fungal Endophyte Infection, Elevated Temperature, and Precipitation

Abstract: Tall fescue (Schedonorus arundinaceus (Schreb.) Dumort., nom. cons.) can form a symbiosis with the fungal endophyte Epichloë coenophiala, whose presence often benefits the plant, depending on plant and fungal genetics and the prevailing environmental conditions. Despite this symbiosis having agricultural, economic, and ecological importance, relatively little is known regarding its response to predicted global climate change. We quantified the ecophysiological responses of four tall fescue genetic clone pairs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
1
29
0
3
Order By: Relevance
“…Our results of relatively limited importance of endophyte infection to tall fescue abiotic stress tolerance are not unheard of: not all studies have shown benefits of endophyte infection to tall fescue under stressful conditions (MacLean et al, 1993 ; Richardson et al, 1993 ; Elbersen and West, 1996 ; Buck et al, 1997 ). Some have shown no effects (Arachevaleta et al, 1989 ; Belesky et al, 1989 ; Hill et al, 1996 ), and work performed in this same project found that E+ tall fescue experienced more mortality than E− after 1 month of +heat treatments (Brosi, 2011a ) and that tall fescue's response to the treatments is under plant genetic control, in addition to being impacted by Epichloë presence and strain type (Bourguignon, 2013 ). We did not control for plant genetic background in this experiment, as we were interested in measuring changes to the population, and it is possible that differing fescue genotypes in our project responded to both climate treatments and endophyte presence in contrasting ways (West, 2007 ), which might have hampered our ability to detect an endophyte-associated response to the climate treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results of relatively limited importance of endophyte infection to tall fescue abiotic stress tolerance are not unheard of: not all studies have shown benefits of endophyte infection to tall fescue under stressful conditions (MacLean et al, 1993 ; Richardson et al, 1993 ; Elbersen and West, 1996 ; Buck et al, 1997 ). Some have shown no effects (Arachevaleta et al, 1989 ; Belesky et al, 1989 ; Hill et al, 1996 ), and work performed in this same project found that E+ tall fescue experienced more mortality than E− after 1 month of +heat treatments (Brosi, 2011a ) and that tall fescue's response to the treatments is under plant genetic control, in addition to being impacted by Epichloë presence and strain type (Bourguignon, 2013 ). We did not control for plant genetic background in this experiment, as we were interested in measuring changes to the population, and it is possible that differing fescue genotypes in our project responded to both climate treatments and endophyte presence in contrasting ways (West, 2007 ), which might have hampered our ability to detect an endophyte-associated response to the climate treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Plugs originated from an existing adjacent field. For more details on site characteristics and stand establishment see Brosi ( 2011a ), Slaughter ( 2012 ), and Bourguignon ( 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…The information in the establishment year of the sward, within and among sites, is more variable than that of a full production year because the former is more dependent on the sowing date and environmental conditions during the first months after sowing. The convenience of using data from the second year onwards was noted earlier by Bourguignon (). In accordance with the above, the last two full production years were used for a correlation analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Assuming the endophytes are viable at sowing, endophyte-infected plants would be introduced into the environment. Epichloë infected agricultural grass species have a selective advantage in hot and dry environmental conditions [49][50][51] and under stressed conditions such as herbivory [52][53][54]. Climate change could result in environmental conditions that are more conducive to survival of infected grasses, which may increase their distribution to a level that endophyte-infected plants could dominate grasslands.…”
Section: Discussionmentioning
confidence: 99%